A NATIONAL POLICY ON INDONESIA’S INTEGRATED WATER RESOURCE CONSERVATION MANAGEMENT - Chay Asdak; Yulizar Yulizar; Subiyanto Subiyanto (Indonesian Journal of Forestry Research, 2023)
Changes in the global precipitation would affect Indonesia to improve the water resources management system. As most watersheds are in the critical stage nowadays, it is extremely important to develop a new plan and policy on water conservation which integrate the most important parameters reasonably. This has a purpose to ensure that water resources are available for all activities purposes within the area, especially for the future time period. Integrated Water Resources Conservation Management (IWCM) is one of the promising approaches that mainly developed through the participation of all stakeholders. This participation brings the equal responsibility to protect and manage the water resources in a sustainable way, which might differ from one to another area in Indonesia. Therefore, it is important to bring up local practices on water conservation management. The approach strategies that provided in this paper could improve the water national policy in Indonesia. Furthermore, it also could minimize the gap of the current regulation between local and national levels.